The interfaces of the reformist advocacy thought of Sheikh Al-Fadhil Al-Wartalani (Journal of the College of Basic Education, 2023)
The interfaces of the advocacy thought of Sheikh Al-Fadil Al-Wartalani played a prominent role in the dark conditionsThe hardship that Algeria went through as a result of French colonial control; Ortlani was able to translateThose reformist advocacy facades in order to deepen Arabism and Islam and preserve the Algerian personality;His continuous calls were shown through his sermons, lectures and newspapers moreover that destinationsHis advocacy idea was not present inside Algeria and the Arab world, but rather exceeded that, especially in FranceThe events and activities of the polite clubs founded by Al-Wartlani had a distinguished presence and responded toTo the wishes of many of the Algerian community, workers and students, and this drew the attention of the French authorities to the limitOne of his activities is to demand independence; Therefore, Al-Wartalani left clear imprints in France through facadesan idea; These advocacy facades coalesced with the principles of the 1954 revolution to increase the strength and enthusiasm of the revolutionTo bear fruit at the end of the era of freedom and independence.